Dinamika Pendekatan Interdisipliner: Hambatan dan Proyeksi dalam Penelitian Studi Islam - -, Arif Rahmat Triasa; -, Mhd. Ilham Armi; Al Shaleh, Masnur; Hilmi, Wahyu (Jurnal Studi Islam dan Sosial, 2023)
Interdisciplinary research is becoming a major focus in academic science and policy. Islamic Studies has adopted this approach, especially in addressing social issues such as gender, environment, and pluralism. Although controversial, interdisciplinary research in Islamic studies is considered essential for understanding the complexity of life and solving the problems of this age. This research is a literature study that describes the dynamics of the interdisciplinary approach in Islamic studies, including its obstacles and projections. Descriptive analysis is used to get the right and appropriate results to answer the existing problem formulations. Data collection is carried out systematically and structured by using literature and data relevant to the topic of the interdisciplinary approach in Islamic studies with the dialog of the concept of challenges and prospects. In Islamic studies, the interdisciplinary approach has received attention due to the complexity of religious phenomena. However, cognitive barriers arise from epistemological differences and difficulties integrating concepts, while intellectualism barriers are related to methodological conflicts, personal disagreements, and language factors. Awareness and collaborative efforts are needed to overcome these barriers in developing interdisciplinary research in Islamic studies. Interdisciplinary approach in Islamic studies is increasingly relevant in the face of the complexity of contemporary issues. It is important to maintain consistency with Islamic principles and understand the religion from various perspectives. Although there are pros and cons to this approach, interdisciplinary research can overcome cognitive barriers and intellectualism. Awareness and support for interdisciplinary cooperation is key to advancing this research.